Management of root-knot nematode, Meloidogyne incognita infesting black pepper (Piper nigrum) under field conditions - RAJKUMAR; PERVEZ, RASHID; SUREKHA, R (The Indian Journal of Agricultural Sciences, 2026)
The present experiment were conducted during 2020, 2021 and 2022 at the ICAR-Central Plantation Crops Research Institute, Kasaragod, Kerala for the management of the root-knot nematode, Meloidogyne incognita, infesting black pepper (Piper nigrum L.) cv. Panniyur-1 using a talc-based formulation of Trichoderma harzianum [ICAR-Indian Institute of Spice Research (ICAR-IISR) and ICAR-Central Plantation Crop Research Institute (ICAR-CPCRI) isolates] and Pochonia chlamydosporia (ICAR-IISR isolate), neem cake, and carbosulfan 25 ec (standard check). The experiment was laid out in a randomised block design (RBD). The results indicated that P. chlamydosporia (84 and 72%, respectively) and carbosulfan (91 and 79%, respectively) both exhibited the highest decreases in M. incognita populations in the soil and root, respectively compared to the control. Maximum yield was recorded in carbosulfan (25.86 kg) and P. chlamydosporia (24.32 kg) treated plants in comparison to the control (9.07 kg). P. chlamydosporia (ICAR-IISR isolate) was found promising against M. incognita to reduce the population buildup in the fields, thus, indicating that there exists a scope for management of nematode diseases for organic production of black pepper and better yield to sustain the additional income of the farmer.